Ambient backscatter communication networks - Hoang, Dinh Thai 1986-; Niyato, Dusit 1978-; Kim, Dong In 1958-; Huynh, Nguyen Van ca. 20./21. Jh; Gong, Shimin ca. 20./21. Jh (Cambridge University Press, 2020)
Understand the fundamental principles and applications of ambient backscatter technology with this authoritative review. Covering both theory and practical engineering, leading researchers describe and explain hardware design, network design, and signal processing, and discuss architectures, protocols, communication methods, open research issues, emerging applications, and advanced system models with innovative solutions. This is an essential tool for graduate students, researchers, engineers, developers, and entrepreneurs